PERAN ORANG TUA DAN MASYARAKAT DALAM MENDUKUNG PENDIDIKAN BERMUTU PADA SDN BENUA ANYAR 4 BANJARMASIN - Ahmad Farhan Nashar; Alya Nabila; Karella Lichesya Feithjeria AS; Rifa’atul Mahmudah; Ahmad Suriansyah; Aslamiah, Aslamiah (Journal of Innovation Research and Knowledge, 2025)
This study aims to analyze the strategic roles of Parents and Community in supporting educational quality at SDN Benua Anyar 4 Banjarmasin. The research methodology employed a descriptive qualitative approach using interviews, observations, and documentation. The research subjects included the School Principal. The findings reveal that parental and community contributions are highly significant in supporting quality education, reflected through active participation in school activities, providing moral and material support, and involvement in educational decision-making processes, resulting in no serious obstacles in the partnership between the School, Parents, and Community. The factors influencing such support include awareness of education's importance, educational levels, and the community's socio-economic conditions. The research concludes that synergistic collaboration among Schools, Parents, and Community is the key to creating a quality and sustainable educational environment.